Job Stress manifestations and its associated factors among secondary school teachers in Kuching division - Irwilla, Hj. Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2013)
The teacher remains one of the most stressful occupations worldwide. stressful working conditions can impact employee well-being indirectly by contributing to negative health behaviours or by limiting an individual's ability to make positive changes to lifestyle behaviours, such as smoking and sedentry behaviour. However there is not much study on job stress manifestation done in Sarawak.